Mind the gaps: identifying opportunities in mental health assessment and mental health certificate completion in rural and remote NSW, Australia. (September 2020) - Davis, Martin; Juratowitch, Rodney; Lamont, Scott; Brunero, Scott
Abstract: Objective: This study aimed to examine the quality of mental health certificate (MHC) completion in rural and remote New South Wales, to include the determination of those identified as mentally ill or mentally disordered, and subsequent processes thereafter. Methods: MHCs were collected from April 2016 to March 2017. A de-identified review was undertaken and audited for completion of mandatory criteria. Data were separated by three groups of completing health practitioners, and descriptive and inferential statistics calculated to assess for differences between groups. Results: A total of 277 MHCs were included. Local medical officers were significantly more likely to: have longer assessment periods, indicate mentally disordered rather than mentally ill, and to have the mental health certificate revoked upon reassessment at a declared mental health facility, than their psychiatry or accredited person peers. They were also significantly less likely to complete documentation relating to behaviour personally assessed or observed by others. Conclusion: This study identified inconsistencies in documentation completion between groups, highlighting training opportunities for non-mental health specialists, particularly mental health assessment and lawful detention requirements. Attention to this is warranted within medical training syllabuses, post-graduate training and support programs.